Potential Antibacterials Compounds of Lactic Acid Bacteria (LAB) from Quail Intestine (Coturnix japonica) in Inhibition Growth of Escherichia coli and Salmonella typhimurium - Afdora, Pupimadita Tizar; Ardiyati, Tri; Sjofjan, Osfar; Kalsum, Umi (Journal of Tropical Life Science, 2010)
Quail (Coturnix japonica) is a bird that have high protein content, but vulnerable to digestive diseases. The purpose of this research was to determine the ability of antibacterial compounds of LAB from intestinal quail origin in bacterial growth inhibition test. This research used Completely Randomized Design (CRD) with variable concentrations of Cell Free Supernatant (CFS) for 10, 20, 30, 40, 50, and 60% and bacterial pathogens of the digestive tract of quail (S. typhimurium, E. coli of human origin, and E. coli of bird origin) by using the Minimum inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC). The data obtained were analyzed by Analysis of Variance (ANOVA). The results obtained showed that the bacterium Lactobacillus fermentum and L. salivarius derived from quail intestine can produce antibacterial compounds that could inhibit the growth of Salmonella typhimurium, Escherichia coli (human), and E. coli (bird). Minimum concentration of the addition of CFS from L. fermentum in inhibiting the growth of tested bacteria was 30% for S. typhimurium, 30% for E. coli (human), and 20% for E. coli (bird). While the addition of CFS minimum concentration of L. salivarius in inhibiting the growth of tested bacteria was 20% for S. typhimurium, 20% for E. coli (human), and 10% for E. coli (bird). Keywords: Antibacterials, Lactic Acid Bacteria (LAB), Escherichia coli, Quail, and Salmonella typhimurium.